2019
DOI: 10.1016/j.cmi.2018.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Third-generation cephalosporin and carbapenem resistance in Streptococcus mitis/oralis. Results from a nationwide registry in the Netherlands

Abstract: Knowledge of beta-lactam resistance rates in Streptococcus mitis group bacteria is especially important in neutropenic haematological patients as adequate empirical antibiotic treatment (often including agents like meropenem [1]) is paramount. EUCAST guidelines allow one to infer viridans group streptococci (VGS) beta-lactam susceptibility from benzylpenicillin susceptibility; penicillin-resistant isolates should be tested for individual agents. Few studies reported the association between penicillin resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…In a study that included 1152 VGS isolates collected between 1997 and 2000 from around the world, the penicillin susceptibility rate was 68.6%. 7 More recently, a study of 4164 S. mitis and S. oralis isolates collected in the Netherlands between 2013 and 2017 showed that 87.2% of isolates were susceptible to penicillin, 8 which was similar to the susceptibility rate in a smaller study of isolates from the United States and Europe. 10 Herein, the cumulative penicillin susceptibility rate when combining all species was 83.3% among 12 661 isolates (penicillin susceptibility for S. mitis = 71.0%, S. oralis = 80.9%, non-speciated VGS = 86.3%).…”
Section: Discussionmentioning
confidence: 63%
“…In a study that included 1152 VGS isolates collected between 1997 and 2000 from around the world, the penicillin susceptibility rate was 68.6%. 7 More recently, a study of 4164 S. mitis and S. oralis isolates collected in the Netherlands between 2013 and 2017 showed that 87.2% of isolates were susceptible to penicillin, 8 which was similar to the susceptibility rate in a smaller study of isolates from the United States and Europe. 10 Herein, the cumulative penicillin susceptibility rate when combining all species was 83.3% among 12 661 isolates (penicillin susceptibility for S. mitis = 71.0%, S. oralis = 80.9%, non-speciated VGS = 86.3%).…”
Section: Discussionmentioning
confidence: 63%
“…Among the viridans group streptococci, the S. mitis-oralis subgroup (i.e., S. mitis, S. oralis, S. gordonii and S. parasanguinis) are the predominant IE etiologies. This sub-group is therapeutically problematic, as between 10 and 40% of strains exhibit resistance to penicillins and/or cephalosporins, including ceftriaxone [3,4]. For this reason, the majority of research into S. mitis-oralis antibiotic resistance todate relates to the genetic determinants of penicillin resistance (e.g., [5]).…”
Section: Introductionmentioning
confidence: 99%
“…S. species, including S. milleri group, S. pneumoniae, etc., are the most common bacteria isolated from patients with BAs [ 20 , 21 ]. Third-generation cephalosporin resistance has been reported in less than 8% of Streptococci mitis/oralis isolates in the Netherlands [ 22 ]. According to data from the China Antimicrobial Surveillance Network (CHINET) ( http://www.chinets.com ) in 2021, the resistance rates of Streptococcus viridans to cefotaxime, levofloxacin and clindamycin were 0%, 13.1% and 52.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%